6
$\begingroup$

I was trying to show $$\sum_{n \le x} \frac{d(n)}{n} = \frac{1}{2}\log(x)^2 + 2\gamma \log(x) + O(1)$$ where $d(n)$ is the number of divisors of $n$ and $\gamma$ is the Euler constant using the identity $$\sum_{n \le x}(f * g)(n) = \sum_{n \le x} f(n) G\left(\frac{x}{n}\right)$$ where $G(x) = \sum_{n \le x} g(x)$.

Edit I was using the wrong $f$,$g$ before. Here it is with different $f$,$g$.

For $f(n) = \frac{1}{n}$ and $g(n) = \frac{1}{n}$ this gives $\sum_{n \le x}\frac{d(n)}{n} = \sum_{a \le x} \sum_{b \le x/a}\frac{1}{ab}=\sum_{a \le x}\frac{1}{a}\left(\log(x/n) + \gamma + O(\frac{n}{x})\right)$ since $G(x) = \sum_{n \le x} \frac{1}{n} = \log(x) + \gamma + O(\frac{1}{x})$ by Euler's summation formula. Then apply Euler's summation formula again to get $- \frac{1}{2} \log(x/a)^2 + \gamma \log(x) + O(x^2)$ but this is still wrong.

I can't see at all what I am doing wrong here so it's probably really simple, I would really appreciate if someone could show how to do this or what I've done wrong. Thanks a lot.

$\endgroup$
5
  • 3
    $\begingroup$ You may use $f(n) = g(n) = 1/n$ to derive the estimation. $\endgroup$ – Sangchul Lee May 8 '11 at 4:48
  • $\begingroup$ I get your result by a lengthy summation, if necessary I can type it out. But you should know that you have convolution incorrect: $$ $$ en.wikipedia.org/wiki/Dirichlet_convolution $\endgroup$ – Will Jagy May 8 '11 at 5:48
  • 1
    $\begingroup$ @Will: Yes, it is true. It follows from the estimate $\sum_{n \le x} d(n) = x\log x + (2\gamma -1)x + O(\sqrt{x})$. Apply Abel's identity with $f(t) = 1/t$ and you get the above. I believe this is even an exercise in Apostol's Analytic Number Theory book. $\endgroup$ – Aryabhata May 8 '11 at 6:12
  • $\begingroup$ @sos440, thanks - I tried using this but I still don't get the right answer. $\endgroup$ – quanta May 8 '11 at 10:50
  • $\begingroup$ /Tom M. Apostol/Introduction to Analytic Number Theory, Volume 1/Chapter 3/Exercise 2 $\endgroup$ – nature1729 Jul 2 '14 at 10:03
7
$\begingroup$

Let's start at $$ \sum_{n \leq x} \frac{d(n)}{n} = \sum_{n \leq x} \frac{1}{n} \left( \log \left( \frac{x}{n} \right) + \gamma + O\left( \frac{n}{x}\right) \right).$$ Proceeding, $$ \begin{eqnarray*} & = & \sum_{n \leq x} \left( \frac{1}{n}(\log x + \gamma) - \frac{\log n}{n} + O\left( \frac{1}{x}\right) \right) \\ & = & (\log x + \gamma)(\log x + \gamma + O(1/x)) + O(1) - \sum_{n \leq x} \frac{\log n}{n} \\ & = & \log^2 x + 2\gamma \log x + O(1) - \sum_{n \leq x} \frac{\log n}{n}. \end{eqnarray*}$$ Since $f(x) = \log x / x$ is decreasing for large $x$, we may write $$ \sum_{n \leq x} \frac{\log n}{n} = \int_{1}^{x} \frac{\log u}{u} \, du + O(1) = \frac{1}{2}\log^2 x + O(1), $$ which completes the calculation.

$\endgroup$
4
$\begingroup$

I don't think $f*g$ is actually $d(n)/n$ in your case. What might help would be to write

$\sum_{n \le x} \frac{d(n)}{n} = \sum_{n \le x} \sum_{a \, b = n} \frac{1}{n} = \sum_{a \, b \le x} \frac{1}{ab}$

$\endgroup$
1
  • $\begingroup$ This is the right way, we can actually show that the error term is $O(\log x/\sqrt{x})$. $\endgroup$ – Xiang Yu Apr 12 '16 at 14:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.